Battery power management in heavy-duty HEVs based on the estimated critical surface charge. (7th December 2012) - Lee, Tae-Kyung; Kim, Youngki; Rizzo, Denise M.; Filipi, Zoran S.
This paper proposes a battery power management strategy using Critical Surface Charge (CSC) information estimated by Extended Kalman Filter (EKF) in real time. The insight from CSC characterisation is used to propose a novel approach for supervisory control design of a series Hybrid Electric Vehicle (HEV). The underlying phenomenon determining the battery allowable power limits is closely connected to the CSC. The estimated CSC is processed with a Finite Impulse Response (FIR) filter to smoothen short-term fluctuations and highlight longer-term trajectories. The battery allowable power limits are adjusted based on the filtered CSC information to prevent undesirable battery operations.